ENHANCING STUDENTS’ COMMUNICATION SKILLS THROUGH INTERACTIVE PEDAGOGIES: A MIXED-METHODS APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Communication skills are fundamental to students' academic achievement and future professional success. In a globalized, digitally connected world, students must be able to express ideas clearly, collaborate effectively, and engage in meaningful discourse across diverse settings. This study explores pedagogical strategies to develop students’ communication skills, focusing on both verbal and non-verbal competence. Through a mixed-method approach involving 120 students, including a cohort from the Tashkent University of Applied Sciences, and a team of educators, the research assesses the impact of task-based learning, collaborative activities, and technology-enhanced instruction. The findings indicate that active participation in communicative tasks, peer interaction, and scaffolded instruction significantly enhance students' fluency, confidence, and critical thinking skills. Implications for curriculum design and teacher training are discussed.